Farewell, tick - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
With 1.5 million from the EU, the CARIFORUM Agricultural and Fisheries Programme based in Trinidad and Tobago and FAO are giving the final push to eradicating the Tropical Bont Tick in the English speaking Caribbean (See Spore 85, p 9). After good...